2018
DOI: 10.1111/nyas.13693
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration and deceleration at constant speed: systematic modulation of motion perception by kinematic sonification

Abstract: Many domains of human behavior are based on multisensory representations. Knowledge about the principles of multisensory integration is useful to configure real-time movement information for the online support of perceptuomotor processes (motor perception, control, and learning). A powerful method for generating real-time information is movement sonification. Remarkable evidence exists on movement-acoustic real-time information being effective in behavioral domains (music training, motor rehabilitation, sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Kinematic movement sonification can provide information for perception and action for humans, being classified as musical. This result corresponds to other studies with movement sonification [8,14,27,55].…”
Section: Discussionsupporting
confidence: 92%
“…Kinematic movement sonification can provide information for perception and action for humans, being classified as musical. This result corresponds to other studies with movement sonification [8,14,27,55].…”
Section: Discussionsupporting
confidence: 92%
“…According to Effenberg et al, 8 convergent sensory feedback, which shares a high level of spatiotemporal proximity, can get implicitly fused to promote intermodal learning (in this case auditory and proprioceptive). 10 Here, an additional inference can be drawn from literature emphasizing the importance of intermodal knowledge for obtaining spatial knowledge of the body in space. 52,53 Likewise, evidence from neuroimaging studies also supports the notion that a high level of stimulus-response consistency (meaningful organization of perceptual and motion events) can promote sensorimotor coactivations 27 and motor priming.…”
Section: Figure 2 Absolute Mean and Standard Error Of Repositioning mentioning
confidence: 99%
“…3,8 Research conclusively suggests that mapping a performer's action with real-time auditory feedback can enhance both the perceptuomotor representations in the brain and motor performance. [8][9][10][11][12] Strong influence of real-time auditory feedback on motor performance was thought to be due to its influence over the proprioceptive modality. [13][14][15][16] Hasegawa et al, 16 for instance, reported that training with auditory augmented biofeedback might facilitate the integration of auditory and proprioceptive systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, auditory system reacts faster than the visual system and its proper frequency is well adapted to provide augmented information during movement execution (Vinken et al 2013). In particular, the use of real-time continuous auditory feedback directly related to movement parameters is called "movement sonification" (Bevilacqua et al 2016;Dubus and Bresin 2013). In such systems, initially developed for artistic purpose, the sound is continuously modified by the movements of the human performer.…”
Section: General Introductionmentioning
confidence: 99%